2012
DOI: 10.1002/jat.2731
|View full text |Cite
|
Sign up to set email alerts
|

Th2 cytokine‐mediated methimazole‐induced acute liver injury in mice

Abstract: Drug-induced liver injury (DILI) is a major safety concern in drug development and clinical practice. The pathogenesis of DILI usually involves the participation of the parent drug or metabolites that either affect cellular function or elicit an immune response. However, the mechanisms leading to DILI are unknown in most cases. Methimazole (MTZ) is used as an antithyroid drug and is well known to have induced liver injuries such as cholestatic hepatitis in a small number of human cases. Immune-mediated reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…2A). Many researchers have applied GSH-depleted animal models using BSO to evaluate the hepatotoxic potential of several drugs (Nishiya et al, 2008;Shimizu et al, 2009Shimizu et al, , 2011Kobayashi et al, 2012a). Therefore, BSO (700 mg/kg) was intraperitoneally injected 2 hours prior to the oral CBZ administration; however, the plasma ALT levels were not increased ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2A). Many researchers have applied GSH-depleted animal models using BSO to evaluate the hepatotoxic potential of several drugs (Nishiya et al, 2008;Shimizu et al, 2009Shimizu et al, , 2011Kobayashi et al, 2012a). Therefore, BSO (700 mg/kg) was intraperitoneally injected 2 hours prior to the oral CBZ administration; however, the plasma ALT levels were not increased ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have established animal models of drug-induced liver injury, such as trovafloxacilin and sulindac, using lipopolysaccharide to study immune-mediated mechanisms (Shaw et al, 2007, Zou et al, 2009). In addition, it has been reported that GSH-depleted animal models using L-buthionine sulfoximine (BSO), which is an inhibitor of GSH synthesis, are useful for inducing sensitization to liver injury by such drugs as methimazole, tienilic acid, amodiaquine, and ticlopidine via reactive metabolite formations (Nishiya et al, 2008;Shimizu et al, 2009Shimizu et al, , 2011Kobayashi et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetaminophen-induced liver injury can be associated with disturbance of balance of Th1/Th2 cytokines into a Th1-dominant response (Masubuchi et al, 2009). Th2-related immune factors have been activated in methimazole-and flutamide-treated mice Kobayashi et al, 2012). Neutralization with antibody can suppress the hepatotoxicity that further proves the involvement of Th2-related immune factors.…”
Section: T-helper 1 and 2 Cells In Liver Injurymentioning
confidence: 96%
“…The mechanism could be related to the fact that it is a hepatic-metabolised drug. The pathogenesis of the liver injury usually involves the participation of the parent drug or metabolites that may affect cellular function or trigger an immune response (22). Immunemediated reactions were also suggested to play a role methimazole-induced acute liver injury.…”
Section: Discussionmentioning
confidence: 98%